Socio-economic and institutional Supports for influencing farmer’s understanding of climate change and their adaptation strategies in Senegal, West Africa - Zagre, Inoussa; Worou, Nadine Omonlola; Akinseye, Folorunso Mathew; Kone, Mama; Faye, Aliou (2023)
The document discusses the socio-economic and institutional supports influencing farmers' understanding of climate change and their adaptation strategies in Senegal, West Africa, presented at the Climate Forum 2023 in Mittweida, Germany.